Лабрис (Семибратнее городище) и синды (по материалам полевых исследований Боспорской экспедиции ИИМК РАН в 2001-2008 гг.) - Горончаровский, В.А. (Кримське відділення Інституту сходознавства ім. А.Ю. Кримського НАН України, 2009)
Лабрис (Семибратнее городище) расположен в 28 км к северо-востоку от г. Анапа. Своей широкой овальной частью протяженностью приблизительно 360 м он обращен к р. Кубань и в общей сложности занимает площадь около 11 га. Впервые раскопки этого археологического памятника были проведены в 1878 г. В.Г.Тизенгаузеном, ранее исследовавшим известные Семибратние курганы в 3 км от городища. Следующий этап в его изучении связан с работами Н.В.Анфимова в период с 1938 по 1955 гг., когда были вскрыты участки оборонительных стен V-IV вв. до н.э. и позднеэллинистическое каменное здание. Новые данные о Лабрисе получены в ходе полевых исследований Боспорской экспедиции ИИМК РАН, начиная с 2001 г. Лабрис (Семібратнє городище) розташоване у 28 км до північно-сходу від м. Анапа. Своєю широкою овальною частиною протягом приблизно 360 м він повернутий до р. Кубань та в загальному плані займає площу біля 11 га. Уперше розкопки цієї пам.ятки археології були проведені у 1878 р. В.Г. Тизенгаузеном, який раніше досліджував відомі Семібратні кургани у 3 км від городища. Наступний етап в його вивченні пов’язаний з роботами Н.В. Анфімова у період з 1938 по 1955 рр., коли були відкриті ділянки оборонних стін V-IV ст. до н.е. та пізнєелліністична кам’яна споруда. Нові дані про Лабриса отримані під час польових досліджень Боспорської експедиції ІІМК РАН починаючи з 2001 р. The Labrys (Semibratnee city site) is located in 28 km to northeast from the modern city Anapa (ancient Gorgippia) in the valley of lower reaches of the Kuban River. The settlement by wider part about 360 m is inverted to the left coast of the river and covers about 10 hectares. Archaeological exploration of the site has a long history. The first small excavation was lead here in 1878 by Vladimir Tizengauzen, who before that investigated famous so-called Semibratnie barrows, where kings of the Sindoi were buried. He was the first to describe the ancient ruins at a distance of 3 km from the barrows. The second stage in the research of this fortified settlement is constituted by the fieldworks of Nikita Anfimov in 1938-40, 1949-52 and 1954-55 (in the north and northeastern parts of the site). He revealed defensive walls of the 5th-4 th century B.C. with rectangular towers by safety up to 2 m in height and monumental stone building of the middle of the 3rd-1st century B.C. The general capacity of cultural layers of the end of the 6 th century B.C.-1st century A.D. reaches to 3,4 m. Recently the real name of city Λάβρυ[ζ] - is became known from occasionally revealed find of dedicated inscription of the Bosporan king Leukonos I (389/88-349/48 B.C.), where it is spoken about the fight with Octamasades, the son of Sindoi’s king Hekateios, when he has attempted to deprive of power his father. N.Anfimov did not doubt that the city has resulted from social and economic development of Syndoi, which appeared in the close neighbourhood with Greek colonies of Cimmerian Bosporus. The purpose of the present work is the analysis of the new data received during last field researches (since 2001) and attempt to give the vision of separate problems of studying of Sindoi and Sindian kingdom. Certainly we understand, that many supervision and conclusions have preliminary character and demand an additional substantiation.